Drying kinetics and effective moisture diffusivity of purslane undergoing microwave heat treatment - Demirhan, Elcin; Ozbek, Belma (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2010)
The effects of microwave drying on moisture content, moisture ratio, drying time and effective moisture diffusivity of purslane leaves (Portulaca oleracea L.) were investigated. By increasing the microwave output power (180-900W) and the sample amounts (25-100 g), the drying time decreased from 43 to 12.5 minutes and increased from 27 to 54 minutes, respectively. To determine the kinetic parameters, the drying data were fitted to various models based on the ratios of the differences between the initial and final moisture contents and equilibrium moisture content versus drying time. Among the models proposed, the semi-empirical Midilli et al. model gave a better fit for all drying conditions applied. By increasing the microwave output power and decreasing the sample amount, the effective moisture diffusivity values ranged from 5.913x10(-11) to 1.872x10(-10) m(2)/s and from 9.889x10(-11) to 3.292x10(-11) m(2)/s, respectively. The activation energy was calculated using an exponential expression based on the Arrhenius equation.
Keywords: Microwave Drying; Purslane Leaves; Drying Kinetic; Activation Energy; Effective Moisture Diffusivity; PORTULACA-OLERACEA L.; DESORPTION ISOTHERMS; HOT AIR; LAYER; CARROT; APPLE; DEHYDRATION; PARAMETERS; QUALITY; MODEL; Chemistry; Engineering